Morfologia jakości pracy - Unolt, Jerzy (Wydział Prawa i Administracji UAM, 1988)
A category of the quality of work is understood in many ways, what is first of all a consequence of the complexity of that phenomenon. The purpose of the article is to present comprehensively a category of the quality of work of an individual producer, taking into account the elements of its structure. The quality of work may be analysed from the point of view of effects as well as outlays. In the first approach, about the quality decides the result of work, evaluated from the viewpoint of technical and/or economic criteria. However, the possibilities of such evaluations are limited to works which result in material products or services. If work consists in rendering non-material services, the only basis for evaluating its quality are the outlays In the latter case the quality of work is determined by: — the characteristics of work, determining its objective difficulty (complexity of functions, responsibility, strenuousness of activities and material environment conditions); it is the quality required by work; — behaviours of people who perform work (intensity of work, rational use of means of production, lack of defects, promptness of completion, work discipline, initiativeness); it is the realized quality. The lack of a synthetic measure of the quality of individual work makes it necessary to apply to its evaluation various fragmentary measures, the synthesis of which is always burdened with some degree of subjectivism.
Morphology of the quality of work